Function of selected natural antidiabetic compounds with potential against cancer via modulation of the PI3K/AKT/mTOR cascade - Nurcahyanti, Agustina Dwi Retno; Jap, Adeline; Lady, Jullietta; Prismawan, Deka; Sharopov, Farukh; Daoud, Rachid; Wink, Michael; Sobeh, Mansour (Biomedicine & pharmacotherapy, 2021)
Diabetes mellitus (DM) is a metabolic disorder with growing global incidence, as 387 million people were diagnosed in 2014 with an expected projection of 642 million in 2040. Several complications are associated with DM including heart attack, stroke, kidney failure, blindness, and cancer. The latter is the second leading cause of death worldwide accounting for one in every six deaths, with liver, pancreas, and endometrium cancers are the most abundant among patients with diabetes. Phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway plays a vital role in developing a wide array of pathological disorders, among them diabetes and cancer. Natural secondary metabolites that counteract the deleterious effects of reactive oxygen species (ROS) and modulate PI3K/Akt/mTOR pathway could be a promising approach in cancer therapy. Here, 717 medicinal plants with antidiabetic activities were highlighted along with 357 bioactive compounds responsible for the antidiabetic activity. Also, 43 individual plant compounds with potential antidiabetic activities against cancer via the modulation of PI3K/Akt/mTOR cascade were identified. Taken together, the available data give an insight of the potential of repurposing medicinal plants and/or the individual secondary metabolites with antidiabetic activities for cancer therapy.
Gesehen am 07.01.2022